Clinco-Pathological Patterns in Women with Dysfunctional Uterine Bleeding - Rehana Najam; Rana Sherwani; Safia Rana; Seema Hakim; Zeeba Jairajpuri (Iranian Society of Pathology, 2016)
Background: The term dysfunctional uterine bleeding(DUB) refers to any abnormal bleeding from the uterus, unassociated with tumour, inflammation and pregnancy. The histological diagnosis of DUB is very essential for adequate management especially in perimenopausal and postmenopausal females. The present study was undertaken with the aim of evaluating DUB in various age groups, carry out histopathological study of the endometrium and analyze its clinic-pathological patterns. Methods: The study included 500 cases of atypical uterine bleeding, out of which 120 cases of DUB were included based on clinical features and detailed investigations. Study was conducted in Jawaharlal Nehru Medical College, Aligarh Muslim University, between March 2003 to December 2004  Endometrial tissue was collected by D&C procedure and the samples were sent for histopathological evaluation by pathologist. Result: Hyperplasia was the commonest endometrial pathology (20.5%) followed by luteal phase insufficiency (15.6%) and secretory endometrium (13.7%). Endometritis including tubercular endometritis (12.7%), post abortal (5.8%), proliferative (6.8%), polyp (3.9%), atrophic (3.9%), exogenous hormone changes (2.9%) and anovulatory cycles(6.8%) made up for the remaining lesions. Conclusion: DUB occurs secondary to a wide variety of functional and structural abnormalities, warranting a thorough evaluation especially in perimenoupausal females. Menorrhagia is a common symptom and the most likely etiology relates to the patient's age. Significant number of endometrial samples revealed pathology rendering endometrial curetting and biopsy an important procedure. Cervical cytology is a valuable adjunct however histopathology remains the gold standard in diagnosis.